Clinical and molecular delineation of spondylocostal dysostosis type 3. Issue 6 (16th March 2021) - Schuhmann, Sarah; Koller, Heiko; Sticht, Heinrich; Kraus, Cornelia; Krumbiegel, Mandy; Uebe, Steffen; Ekici, Arif B.; Reis, André; Thiel, Christian T.
Abstract :